The richest man in Babylon - George S. Clason read by Denis Waitley (New York, NY Gildan Media Corporation, 2015)
Denis Waitley narrates the classic book written by George S. Claison in 1926, which offers financial advice through a collection of parables set in ancient Babylon. Through their experiences in business and managing their personal affairs, the characters in the parables learn simple lessons in financial wisdom, as relevant in the 21st century as they were in antiquity.
Keywords: Business ethics